2016
DOI: 10.1097/mou.0000000000000329
|View full text |Cite
|
Sign up to set email alerts
|

Role of surgical consolidation in metastatic urothelial carcinoma

Abstract: Purpose of reviewSince the development of systemic combination chemotherapy, postchemotherapy extirpation has been performed in selected patients mainly with locally advanced and/or initially unresectable bladder cancer, and, in very selected patients, surgical consolidation for visceral metastases has also been performed. The purpose of this article was to review and summarize the current evidence for the role of surgical consolidation in metastatic urothelial carcinoma.Recent findingsThe role of metastasecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
1
8
0
1
Order By: Relevance
“…The role of consolidation surgery in aUTC is not as well defined as that in other solid tumors [26]. In concert with previous findings [26], we found that long-term survival in patients undergoing surgery almost exclusively occurred after a favorable response to chemotherapy: Only 1 of 11 patients (9%) survived 3 years when surgery was performed after progression on chemotherapy, as opposed to 8 of the 21 patients Long-Term Survival in aUTC (38%) who were operated following an objective response to chemotherapy. Type of chemotherapy did not seem to affect postsurgery outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The role of consolidation surgery in aUTC is not as well defined as that in other solid tumors [26]. In concert with previous findings [26], we found that long-term survival in patients undergoing surgery almost exclusively occurred after a favorable response to chemotherapy: Only 1 of 11 patients (9%) survived 3 years when surgery was performed after progression on chemotherapy, as opposed to 8 of the 21 patients Long-Term Survival in aUTC (38%) who were operated following an objective response to chemotherapy. Type of chemotherapy did not seem to affect postsurgery outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, some patients can achieve long-term favorable outcomes with this approach. 41 In one series, median survival from time of metastasectomy was 23 months, whereas 5-year OS rate was 33%. 42 In another series, 5-year OS rate from metastasectomy was 28%.…”
Section: Difficult Clinical Questionsmentioning
confidence: 95%
“…On the basis of composite retrospective data, ideal metastasectomy candidates would demonstrate good response to NAC and show disease stability without rapid progression. 41 Fluorodeoxyglucose-positron emission tomography/computed tomography may be more useful than conventional contrast-enhanced computed tomography for assessing postchemotherapy treatment response of nonurinary tract lesions in urothelial carcinoma. 44 Other important characteristics include small disease volume, preferably at a single site, which is accessible for resection with negative margins, and an otherwise good health status.…”
Section: Difficult Clinical Questionsmentioning
confidence: 99%
“…Стоит также отметить, что данные группы препаратов дороги и не всегда доступны. При этом ряд авторов сообщают о допустимости удаления отдаленных очагов в комбинации с системной терапией и возможном влиянии данной стратегии на выживаемость [12][13][14][15][16][17][18][19][20]. Представленный клинический случай показывает возможные способы контроля прогрессирующего метастатического РМП.…”
Section: Introductionunclassified